Selected Aspects Related to Medicinal and Aromatic Plants as Alternative Sources of Bioactive Compounds - Fierascu, Radu Claudiu (Int J Mol Sci, 2021)
Natural compounds obtained from different medicinal and aromatic plants have gained respect as alternative treatments to synthetic drugs, as well as raw materials for different applications (cosmetic, food and feed industries, environment protection, and many others). Based on a literature survey on dedicated databases, the aim of the present work is to be a critical discussion of aspects regarding classical extraction versus modern extraction techniques; possibilities to scale up (advantages and disadvantages of different extraction methods usually applied and the influence of extraction parameters); and different medicinal and aromatic plants’ different applications (medical and industrial applications, as well as the potential use in nanotechnology). As nowadays, research studies are directed toward the development of modern, innovative applications of the medicinal and aromatic plants, aspects regarding future perspectives are also discussed.